2022
DOI: 10.3390/su142416888
|View full text |Cite
|
Sign up to set email alerts
|

Improving Circular Supply Chain Performance through Green Innovations: The Moderating Role of Economic Policy Uncertainty

Abstract: The sudden outbreak and long-term trend of COVID-19 have brought huge attacks and uncertainty to the global economy, forcing countries to introduce various policies frequently to stimulate economic recovery. To realize sustainable development, firms established an environment-friendly economic development model by building a circular supply chain and implementing a green innovation strategy, which is expected to save resources and protect the environment by recycling resources. Based on this background, this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…This aligns with the resource-based view (RBV), which emphasizes the importance of internal resources in gaining a competitive advantage. In the face of policy uncertainties, Liu and Wang's research [35] demonstrates the role of green innovation in fostering circularity. Similarly, Nikseresht et al [149] and Hongquan and Abdullah [13] have demonstrated the beneficial effects of green innovation on sustainable logistics and green supply chain management (GSCM) practices, such as green procurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aligns with the resource-based view (RBV), which emphasizes the importance of internal resources in gaining a competitive advantage. In the face of policy uncertainties, Liu and Wang's research [35] demonstrates the role of green innovation in fostering circularity. Similarly, Nikseresht et al [149] and Hongquan and Abdullah [13] have demonstrated the beneficial effects of green innovation on sustainable logistics and green supply chain management (GSCM) practices, such as green procurement.…”
Section: Discussionmentioning
confidence: 99%
“…The research by Hongquan and Abdullah [13] This research contributes to the ongoing conversation surrounding green supply chain management (GSCM) by examining the interplay between green innovation strategies, logistics practices, and the complexity of supply chain operations. Drawing upon the findings of Liu and Wang [35] regarding the impact of green innovation on enhancing the performance of circular supply chains in times of economic uncertainty, this study aims to investigate the ways in which these strategies contribute to the reinforcement of resilience. This study emphasizes the value of teamwork in addressing supply chain challenges and incorporates research on eco-technological innovation by Nureen et al [18].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, they enable improved surveillance and tracking tools that enable organizations to operate efficiently and proactively via sustainability (Xu et al, 2023). As a result, companies recently tend to concentrate on green metrics strategies, which minimized pollution procedures, energy consumption approaches, and resource and costs saving plans (Liu & Wang, 2022). These tools additionally increase individual and social awareness and create a more secure workplace in the industrial environment (Kabir & Aminul Islam, 2021).…”
Section: Hypothesis Developmentmentioning
confidence: 99%